Definition of principles of tourist traffic organization on narrow-gauge railways - Bobyl, Volodymyr; Martseniuk, Larysa; Hnennyi, Oleh; Bozhok, Nataliia (Technology audit and production reserves, 2017)
To increase the competitiveness of railway transport the authors propose to develop of railway tourism in Ukraine. The article aims are: to design an optimal the classification of narrow-gauge transfers and tourist travels depending on the travel purpose, type of rolling stock, travel term, and the service areas; to determine factors that play main role for the development of tourist traffic on the narrow gauges; to develop a methodological approach that is based on the principle of determining the actual number of passengers and revenues from tourist transportations on the certain routes. The methodical approach to determining the cost of tourist traffic by railway and road transport was further developed. This approach is based on the principle of determining the actual number of passengers and revenues from tourist transportations on the certain routes. It was taken into account the attractiveness of the route, price for tourist vouchers or travel tickets, minimization of the rolling stock number and the cost of construction and income of the company. Moreover, the authors set a goal to develop a methodical approach to determine the costs of the company that will organize transportations on the specific tourist route. As a result of the proposed measures one can expect increase of passenger traffic on the railroad, image improvement of the Ukrainian railways within the country and abroad, attraction of additional funds to renew the outdated infrastructure and rolling stock, restoration of the objects of cultural and historical significance, creation of new jobs, and restraining of migration processes in western Ukraine.